PREFIKS ME- DALAM CERPEN DURIAN KARYA DJENAR MAESA AYU - Cahyani, Via (MIMESIS, 2021)
This study aims to examine the "me-" prefixes in the short story Durian by Djenar Maesa Ayu based on the process of reciting and the function of said prefixes by inflective prefix and derivative prefix. This short story is interesting to be studied because by knowing the meaning of the story, the message submitted by the author can be well received by the readers. This study is made by using a descriptive qualitative method together with a morphological approach as the basis of its analysis. This study is made by using some data collection techniques which include reading techniques and note taking techniques. The results of this study proves that the author predominantly uses phoneme conservationin the affix processing. In addition, there is a prefix function found in the "me-" prefixes which forms a semi-transitive verb that has beenÂ contained in a word "memancing".Â